Relación del nivel de conocimiento y práctica del Modelo SOAPIE en la Calidad de las anotaciones de los profesionales de Enfermería del Hospital II EsSalud, Vitarte - Castillo Asencios, Karen Liliana (2019)
The aim of this study was to determine the relationship of the level of knowledge and practice model SOAPIEon the quality of the annotations of the nursing staff of Hospital II EsSalud Vitarte. The quantitative research wasnon-experimental design and scope transversal descriptive, correlational. The sample included 30 nurses and 90nursing notes. The instruments used were a questionnaire on the SOAPIE model and a checklist that evaluatesSOAPIE practice model and the quality of the entries based on SAP. We found that knowledge and practice in theSOAPIE model relates to minimum percentage in the structure of the nursing notes, also the knowledge level isrelated weakly to the content of those opposed to the practice where the relationship is very strong in the content ofthe notes.